Managing the Margins: Gender, Citizenship, and the International Regulation of Precarious Employment - Vosko, Leah F. (Oxford University Press, 2010)
[E]xplores the precarious margins of contemporary labour markets. Over the last few decades, there has been much discussion of a shift from full-time permanent jobs to higher levels of part-time and temporary employment and self-employment. Despite such attention, regulatory approaches have not adapted accordingly. Instead, in the absence of genuine alternatives, old regulatory models are applied to new labour market realities, leaving the most precarious forms of employment intact. The book places this disjuncture in historical context and focuses on its implications for workers most likely to be at the margins, particularly women and migrants, using illustrations from Australia, the United States, and Canada, as well as member states of the European Union. Managing the Margins provides a rigorous analysis of national and international regulatory approaches, drawing on original qualitative and quantitative material. It innovates by analysing the historical and contemporary interplay of employment norms, gender relations, and citizenship boundaries. –Publisher's description
https://academic.oup.com/book/26113
Keywords: Employment; Employment. Foreign workers. Women; Employment. Women; Law and legislation. Foreign workers; Law and legislation. Temporary employment; Law and legislation. Women; Legal status; laws; etc. Part-time employment